2012
DOI: 10.4081/hr.2012.e19
|View full text |Cite
|
Sign up to set email alerts
|

Translocation t(11;14) (q13;q32) and Genomic Imbalances in Multi-Ethnic Multiple Myeloma Patients: A Malaysian Study

Abstract: More than 50% of myeloma cases have normal karyotypes under conventional cytogenetic analysis due to low mitotic activity and content of plasma cells in the bone marrow. We used a polymerase chain reaction (PCR)-based translocation detection assay to detect BCL1/JH t(11;14) (q13;q32) in 105 myeloma patients, and randomly selected 8 translocation positive samples for array comparative genomic hybridization (aCGH) analysis. Our findings revealed 14.3% of myeloma samples were positive for BCL1/JH t(11;14) (q13;q3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…To that end, we compared microarrayed samples of human cancers paired with their normal organ tissue samples. Using a public dataset of RNA profiles reported from 43 pairs of breast cancer and normal breast samples [ 32 ], we determined that approximately two-thirds of the breast cancers showed increased RPL24 transcript levels relative to their matched normal breast sample (Figure 1a ). The entire group of tumor samples exhibited a significant 20% mean overall increase in RPL24 expression levels (p = 0.001), indicating that transcriptional upregulation of RPL24 commonly occurs in human breast tumorigenesis (Figure 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…To that end, we compared microarrayed samples of human cancers paired with their normal organ tissue samples. Using a public dataset of RNA profiles reported from 43 pairs of breast cancer and normal breast samples [ 32 ], we determined that approximately two-thirds of the breast cancers showed increased RPL24 transcript levels relative to their matched normal breast sample (Figure 1a ). The entire group of tumor samples exhibited a significant 20% mean overall increase in RPL24 expression levels (p = 0.001), indicating that transcriptional upregulation of RPL24 commonly occurs in human breast tumorigenesis (Figure 1b ).…”
Section: Resultsmentioning
confidence: 99%
“…The ATP8B4 gene can encode a P4-ATPase flippase complex, a member of the cation transport ATPase (P-type) family and type IV subfamily ( 27 ). Ni et al ( 27 ) suggested that ATP8B4 may be a potential prognostic marker and a therapeutic target in the treatment of patients with multiple myeloma who are B-Cell chronic lymphocytic lymphoma/small lymphocytic Lymphoma (BCL)-1/JHt(11;14)(q13;q32) translocation positive.…”
Section: Discussionmentioning
confidence: 99%
“…It is frequently associated with genetic abnormalities such as chromosomal loss and translocation events 75,76 . In a Malaysian study in 2012, SLy2 was identified as a gene located within a chromosomal aberration region in 105 MM patients 77 . Subsequently, Amend and colleagues reported a large chromosome deletion in MM patients affecting the complete SLy2 ‐coding gene section and probably leading to a total loss of SLy2 78 .…”
Section: Sly2mentioning
confidence: 99%